The "eucharistic words of Jesus": an unnoticed silence in our earliest sources - O'Loughlin, Thomas (The Society for Liturgical Study, 2014)
There is a very long standing interest in the 'eucharistic words of Jesus' among both theologians and biblical scholars. However, the words that are given in the Synoptic Gospels are not eucharistic (in the sense of being Jesus' words of blessing / thanking God) but merely what were considered his instructions to the disciples about what they were to do. In effect, we have rubrics for praxis and/or an explanation of praxis, rather than prayers.